Functional finance: A comparison of the evolution of the positions of Hyman Minsky and Abba Lerner - Larry Randall Wray (Levy Economics Institute of Bard College, 2018)
This paper examines the views of Hyman Minsky and Abba Lerner on the functional finance approach to fiscal policy. It argues that the main principles of functional finance were relatively widely held in the immediate postwar period. However, with the rise of the Phillips curve, the return of the Quantity Theory, the development of the notion of a government budget constraint, and accelerating inflation at the end of the 1960s, functional finance fell out of favor. The paper compares and contrasts the evolution of the views of Minsky and Lerner over the postwar period, arguing that Lerner's transition went further, as he embraced a version of Monetarism that emphasized the use of monetary policy over fiscal policy. Minsky's views of functional finance became more nuanced, in line with his Institutionalist approach to the economy. However, Minsky never rejected his early beliefs that countercyclical government budgets must play a significant role in stabilizing the economy. Thus, in spite of some claims that Minsky should not be counted as one of the "forefathers" of Modern Money Theory (MMT), this paper argues that it is Minsky, not Lerner, whose work remains essential for the further development of MMT.
Keywords: B10; B15; B22; B25; B31; B5; E12; E14; E32; E34; E62; H62; 330; Functional Finance; Hyman Minsky; Abba Lerner; Deficit Owl; Budget Deficits; Government Budget Constraint; Phillips Curve; Sovereign Currency; Modern Money Theory